PENGARUH AUDIT TENURE, SPESIALISASI AUDITOR, UKURAN KAP, DAN WORKLOAD TERHADAP KUALITAS AUDIT (STUDI KASUS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2014) - LAILY SUCIATI, ULFAH; NYOMAN ALIT TRIANI, NI (Jurnal Akuntansi AKUNESA, 2019)
This study aims to examine the effect of audit tenure, auditor specialization, the size of the public accounting firms, and workload on audit quality. The population of the data is the entire manufacturing companies listed on the Indonesia Stock Exchange in the period 2010 to 2014. This study used purposive sampling method to select sample from the population. Based on method, sample of 338 manufacturing firms were obtained from the period 2010-2014. The multiple linear regression was used to analyse data. Proxy measurements for audit quality is using discretionary accruals Kaznik model (1999).The result showed that the size of the public accounting firms and workload give impact on audit quality. While audit tenure and auditor specialization do not impact on audit quality.